Mechanisms of luminescence in Î±-Alâ‚‚Oâ‚ƒ:C : investigations using time-resolved optical stimulation and thermoluminescence techniques - Nyirenda, Angel Newton (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2013)
Carbon-doped aluminium oxide, Î±-Alâ‚‚Oâ‚ƒ:C, is a ultra-sensitive dosimeter of topical research interest. The aim of this project was to investigate the dynamics of luminesce in this material. The methods of investigation consisted of thermoluminescence and time-resolved optical stimulation. Thermoluminescence measurements provide information on trap distribution and kinetic parameters of the traps involved in luminescence whereas time-resolved optical stimulation is a handy technique in investigation of luminescence lifetimes and provides an insight into the charge transitions between traps and recombination centres. Measurements were made on samples annealed at a nominal temperature of 900â °C for 15 minutes. The material shows the presence of five thermoluminescence peaks at 37â °C, 160â °C, 300â °C 410â °C, and 480â °C at a heating rate of 0.03k/s when irradiated to 6.0 Gy of beta. The main peak at 160â °C, shows a linear dose response for doses between 0.1 Gy and 10 Gy and then goes sublinear above 10 Gy, the peak at 37â °C shows a sublinear dose response for doses between 0.1 Gy and 10 Gy and appears to saturate thereafter, whereas the dose response of the peak at 300â °C goes from linear to supralinear then apparently quadratic behaviour in the dose range of 0.1 Gy to 16.0 Gy. The trap depth of the main peak, that is, its activation energy as determined below the conduction band, has been approximated at 1.3 eV with a kinetic order of approximately 1.2. Time-resolved optical stimulation has been used to investigate luminescence lifetimes. The mean luminescence lifetime obtained for the sample at ambient temperatures is 35.0Â±1.0 ms. The investigations of the dependence of luminescence lifetimes on measurement temperature show that the material suffers from thermal quenching effects at measurement temperatures above 140â °C with the activation energy of thermal quenching estimated at 1.045Â±0.002 eV. Shallow traps i.e. traps lying close to the conduction band, seem to elongate the lifetimes of optically stimulated luminescence in the material at temperatures between 30â °C - 80â °C due to charge retrapping. The material exhibits both fading and recuperation of the optically stimulated luminescence signal with storage time.
Keywords: Thermoluminescence; Aluminum oxide; Optically stimulated luminescence dating; Radiation dosimetry